Using Phantomless QCT for evaluating BMD evolution in maintenance hemodialysis patients - Yuwen Shen; Qing Hua; Xinyu Pan; Ping Xie; Lianwei Zhang; Linhe Wu; Sitong Yang; Wen Ren; Kefu Liu (Scientific Reports)
Abstract This study was aimed to investigate the evolution of bone mineral density (BMD) in patients with maintenance hemodialysis (MHD) by using phantom-less quantitative computed tomography (PL-QCT). We collected patients with MHD in Suzhou Hospital of Nanjing Medical University from September 2020 to December 2023 as the prospective observation group. BMD of thoracolumbar vertebra, total hip and femoral neck were measured by PL-QCT. Patients with MHD were divided into 9 groups according to hemodialysis duration. Chest CT scans of patients in prospective observation group were collected during the first three months of MHD and 1 year, 2 years, 3 years after dialysis between January 2017 and December 2023 as the retrospective observation group, and BMD of the twelfth thoracic vertebra was measured. According to the BMD changes among the prospective observation group and the retrospective observation group, the evolution of thoracolumbar vertebral BMD, whole hip BMD and femoral neck BMD were comprehensively analyzed. BMD of thoracolumbar vertebra gradually decreased within 36 months in patients with MHD. Thoracolumbar vertebral BMD tended to increase when hemodialysis duration was more than 36–48 months, and thoracolumbar vertebral BMD increased significantly with hemodialysis duration when hemodialysis duration was more than 60 months, and significantly exceeded the BMD before MHD. BMD of total hip and femoral neck gradually decreased within 36 months in patients with MHD. BMD of total hip and femoral neck increased with hemodialysis duration when hemodialysis duration was more than 72 months, but was almost the same as that of the first year of MHD. In the follow-up evaluation of BMD in MHD patients, it is recommended to use QCT to measure BMD in thoracolumbar vertebrae or hip the first 3 years of MHD, and use QCT to measure BMD in thoracolumbar vertebrae to evaluate changes over 5 years of MHD.